The one-state condition : occupation and democracy in Israel/Palestine - Azoulay, Ariella (Stanford studies in Middle Eastern and Islamic societies and cultures., 2013)
Since the start of the occupation of Palestinian territories in 1967, Israel's domination of the Palestinians has deprived an entire population of any political status or protection. But even decades on, most people speak of this rule-both in everyday political discussion and in legal and academic debates-as temporary, as a state of affairs incidental and external to the Israeli regime. In The One-State Condition, Ariella Azoulay and Adi Ophir directly challenge this belief. Looking closely at the history and contemporary formation of the ruling apparatus-the technologies an.